Zentrum und Peripherie Beiträge zum 32. Forum Junge Romanistik in Würzburg (16.-19. März 2016) - Bobineau, Julien; Goldmann, Julius; Goldschmitt, Stefanie; Hesselbach, Robert; Lambrecht, Gabriella-Maria (Forum Junge Romanistik, 2018)
From March 16-19, 2016, the Young Romance Studies Forum on "Center and Periphery" took place at the Julius-Maximilians-Universität Würzburg. In this volume, the dialectical concepts of center and periphery are examined from the perspectives of literary, linguistic, and cultural studies. Their relevance in Romania is examined in the individual contributions on the basis of geographical, spatial, historical, social, and linguistic aspects, in order to include different approaches and methods of analysis. In addition to a heterogeneous approach to the dimensions of the conceptual pair, the volume offers a structured presentation of the individual phenomena studied. The two thematic blocks focus, on the one hand, on diverse literary studies considerations of the dichotomy of the conceptual pair, and, on the other hand, on linguistic conceptions of center and periphery. Thus, new perspectives on both central and peripheral phenomena in Romance studies are opened up, on the one hand by presenting the range of (traditional) centers and peripheries, and on the other hand by referring to current discussions in the context of the two concepts.